2017
DOI: 10.1002/prep.201700179
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior and Decomposition Kinetics of Bis(2,2,2‐trinitroethyl)‐oxalate as a High Energy Dense Oxidizer and its Mixture with Nitrocellulose

Abstract: A new propellant formulation (NC‐BTNEOx) based on bis(2,2,2‐trinitroethyl)oxalate (BTNEOx) as a high energy dense oxidizer (HEDO) mixed with nitrocellulose (NC) matrix was prepared and studied. BTNEOx was prepared and characterized by nuclear magnetic resonance (NMR) and X‐ray diffraction (XRD). Photos of the prepared formulation obtained by scanning electron microscope (SEM) clarified a good mixing of the nitrocellulose (NC) matrix with BTNEOx. A smokeless burning was observed and recorded for the prepared NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In the production of bio-oil from biomass blended with coal, the pyrolysis kinetics of CS, TCS and their blends are important parameters in the effective and efficient design of co-pyrolysers and co-gasifiers. Cai et al (2019) and Abd-Elghany et al (2017) suggested that the thermal decompositions at the start and end of each stage were not stable. As a consequence, the TG data for these ranges have not been considered when calculating the kinetics of co-pyrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the production of bio-oil from biomass blended with coal, the pyrolysis kinetics of CS, TCS and their blends are important parameters in the effective and efficient design of co-pyrolysers and co-gasifiers. Cai et al (2019) and Abd-Elghany et al (2017) suggested that the thermal decompositions at the start and end of each stage were not stable. As a consequence, the TG data for these ranges have not been considered when calculating the kinetics of co-pyrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption band around 1666-1659 cm -1 was assigned to ν а (NO 2 ) associated with CH groups of the glucopyranose rings of CN (position С (2) and/or С (3) ). The intense band around 1646-1631 cm -1 was attributed to ν а (NO 2 ) associated with СН 2 groups of glucopyranose rings of CN (position С (6) ).…”
Section: Resultsmentioning
confidence: 99%
“…This is in good agreement with assignment data of the ν а (NO 2 ) band of primary and secondary alcohols. The substitution of OH group by NO 2 group is known to occur mostly at the С (6) position and inequally at positions С (2) and С (3) , depending on the etherification degree.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studying of the thermal behavior and kinetics of reaction for the new energetic materials are essential to nd suitable new applicable applications. [28][29][30][31][32][33][34][35][36] In this paper, preparation and characterization of TNEF were presented. Propellant formulations based on HTPB as a binder and TNEF and AP as oxidizers have been prepared.…”
Section: Introductionmentioning
confidence: 99%